POC dan Eco-Enzyme dari Limbah Rumah Tangga: Solusi Pertanian Berkelanjutan di Desa Berancah - Nur Asiah; Fery Pianda; Sherly Oktria Minanda; Retno Puspita Anggraini; Annisa Putri Hasibuan; Ibnu Hayyub; Maulana Rizky; Nadya Salwa Zhafira; Nailul Muhimah; Nadzhiful Qolbi; Danuar Sulaiman; Ikhan Kusuma Panuntun Doa; M. Aditya Octoraldo (Unri Conference Series: Community Engagement, 2025)
This article discusses the utilization of household organic waste in Berancah Village, Bengkalis Regency, into Liquid Organic Fertilizer (POC) and eco-enzyme as a solution for sustainable agriculture. The objectives were to increase public awareness and skills in managing organic waste, reduce agricultural production costs, and support environmental sustainability. The method used was a workshop including counseling, identification of raw materials, and practical training in making POC and eco-enzyme using rice washing water and EM4 bio-activator. The fermentation process was monitored for 14 days. The results showed that the community successfully produced POC and eco-enzyme, which are beneficial for enhancing plant growth and improving soil quality. This activity proved to reduce the volume of organic waste while providing an affordable and environmentally friendly fertilizer alternative, thus supporting agricultural productivity and the ecosystem in Berancah Village.